Dual detection of nafcillin using a molecularly imprinted polymer-based platform coupled to thermal and fluorescence read-out. Issue 15 (2nd July 2021) - Hudson, Alexander D.; Jamieson, Oliver; Crapnell, Robert D.; Rurack, Knut; Soares, Thais C. C.; Mecozzi, Francesco; Laude, Alex; Gruber, Jonas; Novakovic, Katarina; Peeters, Marloes
Abstract : Reported here is the production of molecularly imprinted polymer (MIP) films, integrating a fluorescent moiety that serves as both an element for template interaction and signalling, for the thermal and optical detection of the antibiotic nafcillin. Abstract : Reported here is the production of molecularly imprinted polymer (MIP) films, integrating a fluorescent moiety that serves as both an element for template interaction and signalling, for the thermal and optical detection of the beta-lactam antibiotic nafcillin. Fluorescein methacrylate (FluMa ) was synthesized and introduced during the molecular imprinting process as the sole monomer and in a 1 : 1 mixture with methacrylic acid (MAA ), allowing to draw first conclusions on the MIP formation potential of such a rather large and rigid monomer. At first, MIP microparticles containing FluMa were prepared by free radical polymerisation. Optical batch rebinding experiments revealed that FluMa can act as a functional monomer for selective detection of nafcillin; however, the addition of MAA as co-monomer significantly improved performance. Subsequently, thin MIP films containing FluMa were deposited onto functionalised glass slides and the influence of porogen, drying time, and monomer composition was studied. These MIP-functionalised glass electrodes were mounted into a customised 3D-printed flow cell, where changes in the liquid were either evaluated with a thermal device or using fluorescence bright field microscopy. Thermal analysis demonstrated that multiple MIP layers enhanced sensor specificity, with detection in the environmentally relevant range. The fluorescence bright field microscope investigations validated these results, showing an increase in the fluorescence intensity upon exposure of the MIP-functionalised glass slides to nafcillin solutions. These are promising results for developing a portable sensor device that can be deployed for antibiotics outside of a dedicated laboratory environment, especially if sensor design and fluorophore architecture are optimised.